The Role of the Yersiniachelin Siderophore in the Physiology of Yersinia pestis - D. A. Kuznetsova; V. A. Rykova; O. N. Podladchikova (Проблемы особо опасных инфекций, 2023)
Pathogenic bacteria use low-molecular-weight iron chelators – siderophores – to assimilate iron in the host body. Being recognized as virulence factors, these molecules, differing in structural and functional properties, are the subject of the most intensive research in medical microbiology. The present study is devoted to the investigation of yersiniachelin siderophore (Ych) found in the causative agent of plague, Yersinia pestis. The aim of the work was to clarify the role of Ych in the physiology of Y. pestis by comparing the properties of three strains of the plague microbe, differing in Ych production. Materials and methods. Three variants of Y. pestis EV76 strain were used in the experiments: parent strain Y. pestis EV76, its mutant that does not produce Ych due to deletion of three siderophore biosynthesis genes (analogues of ypo1530–1532 in Y. pestis CO92 strain) and a complemented mutant that was transformed by a recombinant pSC-A-5EV plasmid containing Ych biosynthesis genes cloned into the high-copy plasmid vector pSC-A-amp/kan. Comparative analysis of the three strains was carried out in terms of colony morphology, siderophore activity, growth rate, and sensitivity to hydrogen peroxide. Results and discussion. The comparison of these strains has revealed that the secretion of Ych by bacteria at 26 °С ensures the assimilation of iron. At 37 °С, Ych is not secreted into the medium and protects bacteria from the bactericidal action of reactive oxygen compounds. Thus, the study shows that yersiniachelin is able to stimulate the assimilation of iron by bacteria under iron-deficit conditions and has antioxidant properties.